The Globalization of China’s Health Industry Industrial Policies, International Networks and Company Choices - Di Tommaso, Marco R.; Spigarelli, Francesca; Barbieri, Elisa; Rubini, Lauretta (Palgrave Studies of Internationalization in Emerging Markets, 2020)
XIX, 188 p. 46 illus., 9 illus. in color.